2020
DOI: 10.1177/0306624x20969947
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Necrophilic Behaviors in Sexual Homicide: A Criminological Perspective

Abstract: This study aims to empirically explore the patterns of necrophilic behaviors in sexual homicide. More specifically, the study investigates offender, victim, and crime characteristics of sexual homicides where necrophilic acts were perpetrated, to determine whether the primary motivation to kill is associated with the attainment of corpses or whether the post-mortem sexual acts were secondary deviant behaviors. The sample used in this study consists of 109 cases of extrafamilial sexual homicides where post-mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Several hypotheses can be suggested to explain the association between sexual sadism and overkill. First, as mentioned by previous studies (Chopin and Beauregard, 2020a; Holmes, 2017; Keppel et al , 2005), some sadistic sexual murderers may be involved in picquerism. Picquerism is the paraphilia associated with the sexual gratification from the process of penetrating a human body such as cutting, biting or stabbing.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several hypotheses can be suggested to explain the association between sexual sadism and overkill. First, as mentioned by previous studies (Chopin and Beauregard, 2020a; Holmes, 2017; Keppel et al , 2005), some sadistic sexual murderers may be involved in picquerism. Picquerism is the paraphilia associated with the sexual gratification from the process of penetrating a human body such as cutting, biting or stabbing.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the fact that sexual homicides are often described as “unusual”, studies show that these crimes are highly heterogeneous in terms of offender characteristics and crime-commission processes (Higgs et al , 2017). While the combination of sexual elements with the commission of a murder is frightening in itself, studies have shown that there is a gradation in the level of violence used in sexual homicide, with the commission of specific acts such as the insertion of foreign objects (Beauregard et al , 2021; Koeppel et al , 2019; Labuschagne and Theron, 2008), necrophilic behaviors (Chopin and Beauregard, 2020a; Higgs et al , 2017; Stein et al , 2010), dismemberment of the victim’s body (Chopin and Beauregard, 2021), as well as the mutilation of the victim’s body parts (Chan and Li, 2019; Sea and Beauregard, 2019). Among the behaviors described as unusual, overkill is another behavior that has rarely been empirically investigated in relation to sexual homicide.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding post-mortem sexual acts, Higgs et al 59 found no higher use of weapons or unknown victims in sexual homicides. In these cases, Chopin et al 75 suggested four patterns of necrophilia in sexual homicide: preferential, opportunistic, experimental, and sadistic. Only preferential offenders killed victims to have sex with the corpses, while in other offenders, necrophilia was part of a deviant and secondary process.…”
Section: Discussionmentioning
confidence: 99%
“…The brutality and perceived senselessness of SH incidents instill fear within communities and attract the most media attention of all crime categories (Wolfgang et al., 1985), consequently exerting additional pressure on law enforcement agencies. Given that SH cases often exhibit unique characteristics unlike the majority of homicides—extreme acts including foreign object insertion, necrophilia, mutilation, overkill, and dismemberment (Beauregard et al., 2020; Chopin & Beauregard, 2020a, 2020b, 2021a; Koeppel et al., 2019; Stein et al., 2010; Sun et al., 2023)—the intricacy of these cases, coupled with their relatively low occurrence rate, exacerbates the challenges faced by police in solving such crimes (Beauregard & Martineau, 2017). This complexity often leads to these cases becoming cold cases (Davis et al., 2014).…”
Section: Introductionmentioning
confidence: 99%